2007
DOI: 10.1210/en.2007-1350
|View full text |Cite
|
Sign up to set email alerts
|

Astressin B, a Nonselective Corticotropin-Releasing Hormone Receptor Antagonist, Prevents the Inhibitory Effect of Ghrelin on Luteinizing Hormone Pulse Frequency in the Ovariectomized Rhesus Monkey

Abstract: Administration of ghrelin, a key peptide in the regulation of energy homeostasis, has been shown to decrease LH pulse frequency while concomitantly elevating cortisol levels. Because increased endogenous CRH release in stress is associated with an inhibition of reproductive function, we have tested here whether the pulsatile LH decrease after ghrelin may reflect an activated hypothalamic-pituitary-adrenal axis and be prevented by a CRH antagonist. After a 3-h baseline LH pulse frequency monitoring, five adult … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0
5

Year Published

2009
2009
2011
2011

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(41 citation statements)
references
References 60 publications
3
33
0
5
Order By: Relevance
“…Stress has been linked to infertility in adult men (29), lower sperm motility in medical students (30), reduced proceptive sexual behavior (5), and fewer successful impregnations (8) by male rats, as well as lower hatchling survival in free-living European starlings (31). In addition, the effects of malnutrition on reproduction may result from activation of the stress system (32,33), suggesting that the importance of stress effects on the HPG may extend beyond traditional stressors. The HPA axis has also been implicated in aging and the increase in reproductive dysfunction with age (34).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stress has been linked to infertility in adult men (29), lower sperm motility in medical students (30), reduced proceptive sexual behavior (5), and fewer successful impregnations (8) by male rats, as well as lower hatchling survival in free-living European starlings (31). In addition, the effects of malnutrition on reproduction may result from activation of the stress system (32,33), suggesting that the importance of stress effects on the HPG may extend beyond traditional stressors. The HPA axis has also been implicated in aging and the increase in reproductive dysfunction with age (34).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, given the common interaction of HPA and HPG axes across many species and the similarity of GnIH/RFRP actions in birds and mammals (48), the involvement of RFRP in the HPA-HPG interaction investigated here in rats is predicted to be pertinent to most vertebrates. HPA axis activation is implicated in a number of causes of infertility and reproductive dysfunction, including chronic stress and malnutrition (32,33,49), and may significantly influence the efficacy of assisted reproductive procedures in humans (36,50). In addition, chronic stress is of primary concern in captive breeding programs as well as in agricultural breeding programs (51).…”
Section: Discussionmentioning
confidence: 99%
“…Circumstantial evidence, however, suggests an indirect mode of action, as ghrelin effects on LH secretion were inhibited by a non-selective antagonist of corticotrophin-releasing hormone (CRH) [34], and ghrelin was able to inhibit the effect of central elicitors of GnRH/gonadotropin release, such as kisspeptin [29]. In this sense, very recent evidence suggests that ghrelin is able to suppress Kiss1 gene expression at discrete hypothalamic areas [35], thus providing the neuroendocrine basis for, at least part of, its inhibitory effects on puberty onset and gonadotropin secretion.…”
Section: Ghrelin and Puberty Onset: Modulatory Actions In The Male Anmentioning
confidence: 99%
“…Vulliémoz et al [34] have recently indicated that corticotrophin-releasing hormone (CRH) may be involved in the inhibitory actions of ghrelin on LH secretion in rhesus monkey. Moreover, orexin reportedly mediated ghrelin-induced food intake in the rat [6], and we have also clarified that orexin A suppresses LH secretion not only via β-END but also via CRH and urocortin 2 [35].…”
Section: Discussionmentioning
confidence: 99%